Kontribusi Latihan Passing Bawah Berpasangan dan Passing Bawah Ke Dinding Terhadap Ketepatan Passing Bawah - Sudrajat, Muhammad Fadli (Prodi Pendidikan Jasmani Kesehatan dan Rekreasi Universitas Muhammadiyah Sukabumi, 2023)
This research was motivated by the inability of the volleyball players at SDN 1 Pasirjati to make down passes so that when they were about to make a pass the ball was often not directed which resulted in the ball going out of court. This research aims to determine the effect of pair bottom passing practice and bottom passing practice against a wall on volleyball bottom passing accuracy. This type of research uses quantitative research and uses pre-experimental methods. The instrument used in this research was accuracy of passing down (Brumbach) using a sample of 12 volleyball players from SDN 1 Pasirjati. The sampling technique in this research uses a total sampling technique. The research was conducted in the field at SDN 1 Pasirjati. The results of the study showed that the results of the paired down passing exercise had an average increase of 2 times, while the results of the down to the wall passing exercise had an average increase of 3 times, so the results of the down to the wall passing exercise were greater and had a significant influence on increasing the ability to accurately pass volleyball.